Dwa światy, dwa style negocjacji – o kulturowej determinacji w inicjowaniu dyskursu handlowego - Sujkowska-Sobisz, Katarzyna (Stylistyka, 2019)
The author defines a commercial discourse as a model which can be described thanks to analyzed texts which preceded the sales process between tenderers and texts which are or could be results of the sales. In this study, the author is interested in expressions with which – at least two persons in a direct contact during speaking – try to achieve a common financial and sales goal. The author concludes that limitations in initiating commercial talks usually result from: – interlocutors’ social inequality and, therefore, are directly related to the specificcontext of the speech act, – restrictions and sex determination, thus resulting in a wider cultural context, – broadly speaking the spirit of the nation. The author analyzes also differences in the initiation of a commercial discourse in the context of two cultures, using the research category proposed by Michael Foucault, that is dispositif of knowledge.